Urban Dealing with Pandemic: Comparative Responses on Spanish Flu and the Covid-19 Era in Indonesia - Pulung Sumantri; Ahmad Muhajir; Taslim Batubara (IHiS (Indonesian Historical Studies), 2022)
This article compares how the Indonesian, specifically the urban people respond to the pandemic during the history. In 1918, Indonesia, formerly known as the Dutch East Indies, witnessed a pandemic of the Spanish Flu that killed thousands of lives. A century later, Indonesia is once again experienced with the lethal Covid-19 pandemic. The emphasized responses are specific on countermeasures and vaccination programs during the Spanish Flu 1918 and Covid-19 pandemics. The primary source of this research is the archive of annual reports (Kolonial Verslag) Dutch East Indies government 1920 and a report from the Dutch East Indies Civil Health Service (Burgerlijken Geneeskujdigen Dienst), as well as supported by newspapers such as: Sin Po, Oetoesan Hindia, Pewarta Soerabaia, Tjhoen Tjhioe,Bataviaasch Nieuwsblad, and Andalas. This article also aims at understanding how the Indonesian people are handling pandemics, both the Spanish Flu and the Covid-19 pandemics. The action taken by the government in tackling the Spanish flu and Covid-19 pandemic in Indonesia is to issue regulations to reduce activities in the public domain. This regulation has proven successful in reducing the spread of the Spanish flu pandemic in the past and Covid-19 in the present. This research found that Indonesian urban in the past and today have similar points of view, the irrational views and rational views, this is proofed from the emergence of unique, local-rational, and uncontrollable news and rumours because of the amplification of news about the outbreak.  The difference is that in the past, religious responses were expressly confronted with the news but in the present, it is more moderate and open to cooperating with programs from the government. The spectrum from the news of the past outbreaks is not as large as that of the present. Mass media with information technology to social media are further expanding the spectrum from outbreak news to produce more powerful amplifications. It also affects the polarization of the masses that respond rationally and irrationally to the outbreak.